Konsep Persaudaraan dalam Pandangan Islam dan Budha - Arabi, Arianto; Harahap, Indra; Ekowati, Endang (ANWARUL, 2023)
This research aims to find out what is meant by brotherhood and find out the agreements and differences in the concept of brotherhood in the views of Islam and Buddhism. This research method uses library research. Library research is a type of research conducted by reading books or magazines and other data sources to collect data from various literature, both libraries and other places. This researcher uses the Sociology of Religion approach. The sociology of religion approach is an approach that discusses one of the social phenomena, namely religion as a social manifestation. The results of this research show that brotherhood in Islam shows a way that can be taken to build communication on the one hand, and on the other hand, it also gives new enthusiasm to simultaneously carry out teachings in accordance with the instructions of the Qur'an and the examples of the Prophets and Messengers - His. Brotherhood in Buddhism is part of the happiness of life. Loving-kindness or brotherhood is the wish for the happiness of all beings without exception, which is often said to be a pure intention to wish the welfare and happiness of other beings. Brotherhood is the most important part of human life. Fraternity gives rise to positive enthusiasm and motivation, even though in reality not always in the name of brotherhood human life will run in an orderly, good and harmonious way. As major world religions, Islam and Buddhism have their own unique teachings, believed by their adherents on the basis of faith. Universal Islamic teachings and tolerant Buddhist teachings are standard forms that cannot be compared.